A Cross Continental Comparison between India and America: The Global Outsourcing Destination. - Verma, Rahul (2007)
This dissertation takes an in-depth look at the issues related withÃ¢ÂÂOutsourcing Destinations, in particular America and India. It discusses the areas to be analyzed before selecting an outsourcing destination, which affect operational performance within that country. It offers a direct comparison between India and America as Outsourcing destinations in terms of Infrastructure, Government policies, etc. The report also answers a growing global debate. Outsourcing all good?